Metabolizable energy of feeds on diet formulation for broilers - Freitas, Ednardo Rodrigues; Sakomura, Nilva Kazue; Ezequiel, Jane Maria Bertocco; Neme, Rafael; Mendonça, Michele de Oliveira (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the effect of using the metabolizable energy (ME) of feeds, determined by different methods, on diet formulation for broilers. The experiment followed a completely randomized design with four treatments, which consisted in formulating diets using: apparent ME corrected by nitrogen and formulation using apparent ME of feeds, both determined by total excreta collection method with chicks; apparent ME corrected by nitrogen, determined by total excreta collection method with roosters; and true ME corrected by nitrogen of feeds, determined by forced feeding method with roosters. In the initial phase, the higher feed intake, body weight gain, and better feed conversion were obtained from diet based on apparent ME corrected by nitrogen (chicks). During the final phase, birds fed with diet based on true ME, corrected by nitrogen (roosters), showed higher body weight gain and feed conversion. From 1 to 49 days, birds fed according to apparent ME corrected by nitrogen (chicks) showed better performance. The treatments did not affect carcass characteristics. In diet formulation from 1 to 21 days, the apparent ME corrected by nitrogen (chicks) should be considered, and after this age, it is recommended to formulate diets based on apparent ME corrected by nitrogen (roosters) or true ME corrected by nitrogen (roosters).